Keistimewaan Manajemen di Perpustakaan Universitas Pendidikan Indonesia - Seva, Chesa; Setiawati, Linda; Khoerunnisa, Luthfi (Universitas Negeri Padang, 2023)
Library management is an activity that regulates, directs, guides, controls, influences librarians to carry out their duties. The objectives and benefits of library management are so that library management activities can be effective, efficient and productive in achieving the expected goals. Therefore, the author aims to explore the privileges or uniqueness of what management exists in the UPI Library. The author uses qualitative methods based on literature studies and also conducts virtual observations by browsing the UPI Library website and Instagram social media.